2016
DOI: 10.1371/journal.pone.0166016
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Other Characteristics Associated with HIV Viral Load in an Outpatient Clinic

Abstract: Persons living with HIV (PLWH) who are engaged in care, yet not virally suppressed, represent a risk for transmission and opportunity for risk reduction interventions. This study describes characteristics of an outpatient clinic cohort of PLWH by laboratory confirmed viral suppression status and examines associations with demographics and sexual and drug use behaviors gathered through questionnaire. From a sample of 500 clinic patients, 438 were prescribed antiretroviral treatment (ART) and 62 were not. Among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…In agreement with previous studies [32,[35][36][37][38][39][40][41][42], the current study found baseline non-working functional status, low CD4 cell count, advanced WHO clinical stage, and presence of opportunistic infections leads to ART virological failure. Despite this fact, these risk factors are highly interconnected, CD4 cell count is the backbone of immunity construction that helps the human body to protect from the disease and can prevent HIV replication [44].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In agreement with previous studies [32,[35][36][37][38][39][40][41][42], the current study found baseline non-working functional status, low CD4 cell count, advanced WHO clinical stage, and presence of opportunistic infections leads to ART virological failure. Despite this fact, these risk factors are highly interconnected, CD4 cell count is the backbone of immunity construction that helps the human body to protect from the disease and can prevent HIV replication [44].…”
Section: Discussionsupporting
confidence: 92%
“…Social support, such as someone to help with the tasks of starting to rebuild a life, assistance with cooking and assistance to grow crops, all encouraged ART adherence, prevention of opportunistic infections and reduction of viral replication and finally better treatment outcome [33,34,39]. Similarly, it has been reported in other study [40] as social support was a constant predictor of could virological suppression because it help to avoid risky daily behaviors and activities of the patient.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Additionally, methadone, home‐made opioids and amphetamines were the predominant injected substances. The extensive use of varying types of substances, may delay engagement and hinder benefits of HIV and substance use treatment among PWID .…”
Section: Discussionmentioning
confidence: 99%